Armed conflict and maternal health service utilization in Ethiopia’s Tigray Region: a community-based survey - Mache Tsadik; Hale Teka; Mengistu Welday Gebremichael; Hailay Gebretnsae; Awol Yemane; Girmatsion Fisseha; Tesfay Gebregzabher; Gerezgiher Buruh; Fana Gebresellasie; Mulu Tekie; Gebretsadik Kiros; Mahlet Mehari; et al. (BMC Public Health)
Abstract Background Evidence generated on utilization of maternal health services during times of conflict can inform the development of targeted interventions. The deadly war in Tigray caused the health system to collapse. However, utilization of maternal health services is not well documented that might help in design effective interventions applicable during armed conflict. Thus, this study aimed to assess maternal health service utilization and bridge the gap in healthcare provision and support during conflict. . Methods A community-based cross-sectional survey was conducted among mothers of children under the age of 1 year in six accessible zones of Tigray from August 4–20, 2021. The study participants were selected through a random sampling method. The study was conducted during the armed conflict where the access to health services was limited due to the damaged and looted health facilities. A descriptive study was used to characterize the study population and data were presented using proportions and percentages. A Chi-square test was used for categorical variables and a P-value of 0.05 was considered significant. . Results A total of 4,381 participants were included in the study. Modern contraceptives were used by 1002 (22.9%) of women, and injectable contraceptives were the most common method used by 472 (47.1%) women. Likewise, only 830 (36.5%),1956 (47.1%), and 623 (15.0%) respondents reported the use of optimal antenatal care (ANC), skilled delivery, and postnatal care (PNC) in the first 24 h by mothers, respectively. About 34% of women received comprehensive abortion care services. Most delivery services took place in hospitals. Residence has shown a significant difference in using maternal health services at p-value < 0.001. Conclusion The conflict in Tigray has had a profound impact on maternal health services, resulting in a significant disruption that is disproportionately high in rural areas. Immediate action is required to provide access to lifesaving interventions for basic maternal health services. The timely initiation of these services is crucial in addressing the pressing needs of pregnant women and their infants. By implementing comprehensive and targeted interventions, we can mitigate the potential long-term consequences and ensure that maternal health services are effectively reinstated.